Smell perception in virtual spacecraft? A ground‐based approach to sensory data collection - Loke, Grace; Chand, Hirdesh; Chandrapala, Jayani; Peake, Ian; Besnard, Anne; Kantono, Kevin; Iles, Gail; Brennan, Charles; Newman, Lisa; Low, Julia (International journal of food science & technology, 2024)
Summary The study explored context‐driven food odour perception with links to chemical profiling of flavour compounds. Participants rated the intensity of three food odours (vanilla, almond, lemon) in a Neutral context and VR simulation of the International Space Station. The study involved 54 adults aged 18–39 years with no history of motion sickness and/or vertigo. The VR context demonstrated significantly higher intensity ratings for vanilla (P = 0.009) and almond (P < 0.001) odours, compared to the Neutral context. Clustering based on perceived intensity identified that those less sensitive to the odours perceived significantly stronger almond odour in VR (P = 0.011). Gas chromatography–mass spectrometry analysis linked these findings to benzaldehyde, a common compound in both vanilla and almond odours. Therefore, a VR space context may impact odour perception, subject to their volatile composition and individual sensitivity. This underscores VR's potential as a ground‐based analogue for future sensory research, translating across similar settings beyond the space context. Variations in perceived odour intensity may be chemically specific, highlighting the importance of exploring the links between food perception and flavour chemistry. Individual variation in odour sensitivity may also affect food odour perception, wherein particularly volatile compounds within an odour may be more apparent to some than to others.